PENGARUH RASIO NILAI PASAR, LIKUIDITAS, SOLVABILITAS, PROFITABILITAS DAN AKTIVITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR PERTAMBANGAN BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017 – 2019 - Dwi Novita Sari; Aria Masdiana Pasaribu; Ferry Safriandi (Fakultas Ekonomi Universitas Al-Azhar Medan, 2023)
The purpose of this study is to understand the impact of Market Value, Activity, Liquidity, Profitability and Solvency Ratios on Share Prices in the Coal Mining Sub-Sector Manufacturing Business which are listed on the IDX (Indonesian Stock Exchange) for 2017 – 2019. The population in this study totaled 25 , the acquisition of samples in 3 years totaled 12 samples, so that 36 observational data were obtained. The samples taken were applied according to the purposive sampling technique. The use of data analysis methods in the form of multiple linear regression analysis. This study obtains results which can be concluded that partially the variables Market Value Ratio and Liquidity have an impact on Stock Prices, while Solvability, Profitability, and Activity have no impact on Stock Prices. Simultaneously Market Value, Activity, Liquidity, Profitability and Solvability impact the Stock Price.